Living with the law gender and community among the Jews of medieval Egypt - Zinger, Oded (Philadelphia University of Pennsylvania Press, 2023)
No detailed description available for "Living with the Law".
"Living with the Law explores the marital disputes of Jews in medieval Islamic Egypt (1000-1250). Examining the rich documents of the Cairo Geniza, a unique repository of discarded paper discovered in Cairo synagogue, the book recovers the life stories of Jewish women and men working through their marital problems at home, with their families, in the street of old Cairo and in Jewish and Muslim courts. Despite a voluminous literature on Jewish Law, the everyday practice of Jewish courts has only recently begun to be investigated systematically. The experiences of those in legal, social and cultural disadvantage allow us to go beyond the image propagated by legal institutions and offer a view "from below" of Jewish communal life and Jewish law as it was lived"--
Description based on publisher supplied metadata and other sources
Keywords: Jews -- Egypt -- History -- To 1500; Jewish women -- Egypt -- Social conditions -- History -- To 1500; Jewish marriage customs and rites -- Egypt -- History -- To 1500; Jewish courts -- Egypt -- History -- To 1500; Courts -- Egypt -- History -- To 1500; Marriage (Jewish law); Marriage law -- Egypt; Cairo Genizah; Electronic books